Evaluation of Unstimulated Salivary Flow Rate and Oral Symptoms in Menopausal Women - K. Borhan Mojabi; M. Esfahani; H. Jahani Hashemi (Tehran University of Medical Sciences, 2007)
Objective: The aim of the present study was to evaluate unstimulated salivary flow rate and oral symptoms in menopausal women. Materials and Methods: A total of 200 individuals including 100 women in their menopause (case group) and 100 men in the same age range (control group) participated in this analytic descriptive investigation. None of the patients were being treated for any systemic disease or taking any medication. Unstimulated salivary flow rate was measured using the spitting method and the prevalence of oral symptoms was evaluated by filling out a questionnaire. The results were analyzed with ANOVA, chi-square and Student's t-test (P<0.05). Results: The average of unstimulated salivary flow rate was 0.127 ml/min (SD=0.057) in women and 0.214 ml/min (SD=0.105) in men. The prevalence of dry mouth was 50% versus 32%, difficulty in eating dry foods 31% versus 8%, burning sensation in oral mucosa 3% versus 0%, taste reduction, 4% versus 2% and bitter or metallic taste 16% versus 8% in female and male subjects, respectively. Conclusion: A significant difference in salivary flow rate and prevalence of oral symptoms was found between the two groups (P<0.05). Reduced salivary flow rate and a high prevalence of oral symptoms in menopausal women may be related to the hormonal alterations that occur during this period.